Support for Lesbian Couples Navigating Fertility Treatment: An Ecological Systems Perspective. Issue 2 (3rd May 2021) - Rausch, Meredith A.; Wikoff, Haley D.; Newton, Therese
Abstract: In this study, we examined the experiences of support for lesbian couples that navigated the fertility process. Using a sample of seven couples, we explored the support across Bronfenbrenner's Ecological Systems. Participants perceived support from themselves and their partner/spouse, chosen families, family members, other lesbian couples, and the medical community. Participants described stressful factors such as finances, emotional and physical stress, heteronormativity in the medical community, lack of support from family, and loss of pregnancy. The use of Relational Cultural Theory may be helpful to lesbian couples looking to expand their families through reproductive methods.